PIN1 regulates epidermal cells development under drought and salt stress using single-cell analysis - Bawa, George; Liu, Zhixin; Wu, Rui; Zhou, Yaping; Liu, Hao; Sun, Susu; Liu, Yumeng; Qin, Aizhi; Yu, Xiaole; Zhao, Zihao; Yang, Jincheng; Hu, Mengke; et al. (Frontiers in Plant Science, 2022)
Over the course of evolution, plants have developed plasticity to acclimate to environmental stressors such as drought and salt stress. These plant adaptation measures involve the activation of cascades of molecular networks involved in stress perception, signal transduction and the expression of stress related genes. Here, we investigated the role of the plasma membrane-localized transporter of auxin PINIFORMED1 (PIN1) in pavement cells (PCs) and guard cells (GCs) development under drought and salt stress conditions. The results show that drought and salt treatment regulated PCs and GCs development. Further findings identified the different regulation mechanisms of PIN1 in regulating the developmental patterns of PCs and GCs under drought and salt stress conditions. Drought and salt stress also regulated the expression dynamics of PIN1 in pif1/3/4/5 quadruple mutant. Collectively, we show that PIN1 plays a crucial role in regulating plant epidermal cell development under drought and salt stress conditions, contributing to developmental robustness and plasticity.